Maternal and paternal dietary quality, dietary inflammation status, and offspring DNA methylation. (20th October 2021) - Lecorguillé, M; Navarro, P; Shivappa, N; Hébert, JR; Mehegan, J; Kelleher, CC; Suderman, M; Phillips, CM
Abstract: Background: Altered nutritional conditions at early life stages may increase the risk of future disease in offspring. Recent evidence suggests that developmental programming may involve epigenetic mechanisms. However, few studies have evaluated the effect of parental dietary quality on offspring DNA methylation. We investigated the relationships between dietary quality and inflammatory potential of future parents and DNA methylation of their children at nine years. Methods: We used data from the Lifeways Cross-Generation cohort, established between 2001 and 2003 in the Republic of Ireland. Maternal dietary intake during the first trimester and paternal diet of the 12 previous months were assessed with a food-frequency questionnaire. Dietary quality and inflammation were determined by the healthy eating index (HEI) 2015 score and the energy-adjusted dietary inflammation index (E-DII), respectively. The Illumina Infinium HumanMethylationEPIC (EPIC array) assessed methylation levels in saliva samples from 264 children. Dietary associations with DNA methylation at individual CpG sites were examined. Results: After adjusting for multiple tests, maternal HEI-2015 scores were inversely associated with DNA methylation at 1 CpG site (cg21840035, p-value=5.5 × 10-8) located near the PLEKHM1 gene, whose functions involve regulation of bone development. An increase in paternal HEI score was related to lower methylation at one CpG site (cg22431767, p-value=4.1× 10-8) located near cell signaling gene LUZP1. No significant associations between maternal or paternal E-DII and DNA methylation at individual CpG sites were observed. Conclusions: Parental dietary quality in the prenatal period may influence offspring childhood DNA methylation. A better understanding of the nutritional programming effects on epigenetic markers is essential to design public health strategies that could help women to achieve a healthier diet and optimize the health capital of children and future generations. Key messages: Our findings suggest that both maternal and paternal dietary quality may have a long-term influence on the offspring epigenome, expand the current understanding of parental nutritional programming. Replication in other populations with contrasted dietary intake is warranted, with a view to informing public health recommendations to benefit the health of future generations.